Modulation of Protein Stability in Cancer Therapy - Rubin, Eric.; Sakamoto, Kathleen. (Springer US, 2009)
This book contains chapters written by experts in the field of the ubiquitin proteasome system and cancer. The authors have summarized current information on ubiquitin ligases and proteasomes as potential targets for cancer therapy. Topics covered in the book include an overview of ubiquitin ligases, deubiquitinating enzymes, and the proteasome. Specific diseases resulting from deregulated ubiquitin ligases, such as Von-Hippel-Lindau disease and Fanconi anemia are also discussed. Finally, novel approaches and drugs to target proteins involved in sumoylation, ubiquitination, and degradation are described.